Antimicrobial resistance and Neisseria gonorrhoeae multiantigen sequence typing (NG-MAST) genotypes in N. gonorrhoeae during 2012–2014 in Karachi, Pakistan. Issue 1 (December 2016) - Jabeen, Kauser; Bhawan Mal, Pushpa; Khan, Erum; Chandio, Saeeda; Jacobsson, Susanne; Unemo, Magnus
Abstract Background Globally, increasing antimicrobial resistance (AMR) inNeisseria gonorrhoea has led to decreased treatment options for gonorrhoea. Continuous monitoring of resistance is crucial to determine evolving resistance trends inNeisseria gonorrhoea and to suggest treatment recommendations. Quality assured gonococcal AMR data from Pakistan are mainly lacking. This study was performed to determine prevalence and trends of gonococcal AMR and molecular epidemiology of local strains during 2012–2014 in Karachi, Pakistan. Methods Gonococcal isolates (n =  100) were obtained from urogenital specimens submitted to the Aga Khan University Laboratory, Karachi, Pakistan. Antimicrobial susceptibility was determined using Etest and molecular epidemiology was assessed byN. gonorrhoeae multiantigen sequence typing (NG-MAST). Quality control was performed usingN. gonorrhoeae WHO reference strains C, F, G, K, L, M, N, O, and P, and ATCC 49226. Results Susceptibility to spectinomycin, ceftriaxone and cefixime was 100 % and to azithromycin was 99 %. All isolates had low ceftriaxone MICs, i.e., ≤0.032 mg/L. Resistance to ciprofloxacin, tetracycline and penicillin G were 86 %, 51 % and 43 %, respectively. NG-MAST analysis identified 74 different sequence types (STs). Conclusions A highly diversified gonococcal population, 74 NG-MAST STs (62 novel STs) with an increased resistance to penicillin G, ciprofloxacin and tetracycline circulated in Karachi, Pakistan. Fortunately, no resistance to ceftriaxone was detected. Accordingly, ceftriaxone can continuously be recommended as the treatment of choice. However it is recommended to increase the dose of ceftriaxone from 125 mg intramuscularly to 250 mg intramuscularly due to ceftriaxone MIC creep and emerging resistance reported in the region. Furthermore, due to the high level of resistance to ciprofloxacin (86 %) it is essential to exclude ciprofloxacin from the recommended first-line therapy. It is imperative to significantly broaden the gonococcal AMR monitoring with participation from other laboratories and cities in Pakistan.